2016
DOI: 10.1186/s12902-016-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Hashimoto thyroiditis as gold standard to determine the upper limit value of thyroid stimulating hormone in a Chinese cohort

Abstract: BackgroundSubclinical hypothyroidism, commonly caused by Hashimoto thyroiditis (HT), is a risk factor for cardiovascular diseases. This disorder is defined as merely having elevated serum thyroid stimulating hormone (TSH) levels. However, the upper limit of reference range for TSH is debated recently. This study was to determine the cutoff value for the upper normal limit of TSH in a cohort using the prevalence of Hashimoto thyroiditis as “gold” calibration standard.MethodsThe research population was medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This is in agreement with our previous results [14] showing that women with TSH ≥ 2.5 mIU/l have less favorable lipid profiles which is in turn associated with higher oxidative damage to membrane lipids. This is also in line with suggestion to substantially decrease the TSH cut-off for diagnosing of Hashimoto thyroiditis [15].…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with our previous results [14] showing that women with TSH ≥ 2.5 mIU/l have less favorable lipid profiles which is in turn associated with higher oxidative damage to membrane lipids. This is also in line with suggestion to substantially decrease the TSH cut-off for diagnosing of Hashimoto thyroiditis [15].…”
Section: Discussionsupporting
confidence: 91%
“…However, although it is easy to implement, such technique has nearly always been applied using calendar year as time-scale [5][6][7][8]. Only few studies have considered a different time-scale, including deciles of thyroid stimulating hormone value [9], number of telephone calls [10], age [11,12] and time-on-study [13][14][15][16][17]. The latter characterizes the epidemiological studies in which the starting date of the follow-up period can be easily identified (e.g., when the disease is detected or a drug treatment begins).…”
Section: Introductionmentioning
confidence: 99%